2020
DOI: 10.1029/2019je006036
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic Evidence for Volcanic Craters Near Titan's North Polar Region

Abstract: Cassini Radar observations of Titan have revealed diverse landforms resulting from a variety of geologic processes. Many landforms can be unambiguously interpreted as resulting from atmospheric processes (dunes, rivers, and lakes) or impact cratering. Here we argue from morphological evidence such as nested collapses, elevated ramparts, halos, and islands or floor mountains that some of the abundant small depressions in the north polar region of Titan are volcanic collapse craters. A few similar depressions oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 76 publications
(132 reference statements)
0
10
0
Order By: Relevance
“…We can imagine the formation of chemical composition gradients, driven over geological timescales by diffusion, feeding the formation of some pockets of nitrogen which could, at some point, be released abruptly bringing other materials to planetary surface. This kind of mechanism may explain morphological evidence for volcanic activity in Titan's north polar regions (Wood & Radebaugh 2020).…”
Section: Contribution Of Thermal Diffusionmentioning
confidence: 94%
“…We can imagine the formation of chemical composition gradients, driven over geological timescales by diffusion, feeding the formation of some pockets of nitrogen which could, at some point, be released abruptly bringing other materials to planetary surface. This kind of mechanism may explain morphological evidence for volcanic activity in Titan's north polar regions (Wood & Radebaugh 2020).…”
Section: Contribution Of Thermal Diffusionmentioning
confidence: 94%
“…In addition, day-to-night transport from the neutral atmosphere seems to be a significant source of the night side long-lived ions [75]. Titan's thermosphere shows an unexpectedly variable N 2 (Titan's main gaseous species) density that changes by more than an order of magnitude on relatively short timescales (comparable to a few or less Titan days), accompanied by large wave-like perturbations in vertical thermal structure [253,309]. Titan, similarly to Venus, possesses an atmosphere in global superrotation, which extends up to at least 1000 km with a surprisingly high wind speed of 350 m/s [146].…”
Section: Current Knowledgementioning
confidence: 99%
“…Lakes and seas strongly differ in shape [80]. The absence of well-developed fluvial networks at the 300 m-scale of the RADAR/SAR associated with the lacustrine features, in addition to the fact that they seem to grow by coalescence in areas hydraulically and topographically disconnected from the seas, suggests that a distinct scarp retreat process is responsible for the formation and evolution of the lacustrine features on Titan ( [60,62]; Hayes et al 2016Hayes et al , 2017[260]), but do allow for a volcanic collapse or explosion origin [196,310]. Among the hypotheses elaborated on to explain the formation of the lacustrine features, the thermodynamical, geological, and chemical contexts seem to favor the formation by karstic dissolution/ evaporitic processes involving chemical dissolution/crystallization of solutes (soluble molecules) in solvents (in response to the rise or lowering of ground liquids; [55,60,62]).…”
Section: Current Knowledgementioning
confidence: 99%
See 1 more Smart Citation
“…Highly porous regolith has been previously suggested by Hayes et al (2008) for many of the polar terrains of Titan. While there have been non-karstic explanations for the formation of the Titan filled and empty lakes (such as N 2 exsolution blowout or maar formation, see: Mitri et al, 2019;Wood & Radebaugh, 2020), the full range of observed terrestrial karstic morphologies, from polygonal terrains to karstic lakes and poljes, can be adapted to Titan and explained by variations of substrate permeability.…”
Section: Network Formationmentioning
confidence: 99%